Bibliometric Analysis of Risk Factors Contributing to Maternal Mortality: Trends and Research Directions - Haji Ariati; Meitria Syahdatina Noor; Didik Dwi Sanyoto; Nelly Al Audhah; Musafaah Musafaah (Universitas Malahayati Lampung, 2024)
ABSTRACT Maternal mortality remains a significant global health challenge, with high maternal mortality rates in many parts of the world being a key indicator of disparities in maternal health care. While great efforts have been made to reduce these mortality rates, the various contributing risk factors remain a major focus of efforts. This study aimed to conduct a bibliometric analysis of the scientific literature addressing risk factors contributing to maternal mortality over the period 2017 to 2024. In this study, data was obtained from 50 relevant articles retrieved from Google Scholar using Publish or Perish software. The articles were filtered based on relevance and analyzed in depth. The data collected included information on publication year, country of origin, publisher, number of citations, and article type. To generate a comprehensive bibliometric map, VOSviewer was used with the parameters of occurrence of at least 4 and 19 terms, as well as network visualization, overlay, and density. The analysis showed that research on maternal mortality has consistently focused on various risk factors and aspects of maternal health, with a significant emphasis on factors related to pregnancy complications, postnatal care, and socioeconomic health conditions. Developed countries such as the United States are often the primary location of research, indicating a high concentration of studies in these countries. In addition, the research highlighted consistent attention to the importance of adequate health care and specific health issues faced by pregnant women. The analysis also revealed that key themes in the current literature include the management of postpartum hemorrhage, postpartum infections, and the influence of socio-economic factors on maternal health. This study provides valuable insights into current research directions and trends in maternal health and underscores the importance of continuing to identify and mitigate risk factors that contribute to maternal mortality. The findings are expected to guide the development of more effective interventions and health policy strategies that can reduce maternal mortality globally and improve maternal health outcomes worldwide. Keywords: Maternal Mortality, Risk Factors, Bibliometric Analysis, Healthcare Interventions, Research Trends